Individuating 'sparks' and 'flickers' of 'a life' in dance practices with preschoolers: the 'monstrous child' of Colebrook's Queer Vitalism. Issue 5 (2nd September 2016) - Taguchi, Hillevi Lenz; Palmer, Anna; Gustafsson, Lovisa
ABSTRACT: What are the dominant images of the Child in contemporary Western societies? In order to challenge some dominant images of the Child, this essay explores the possibilities of analyzing an experimental dance practice with preschoolers aged 1–2 years with Claire Colebrook's theorizing on 'the war on norms'. Colebrook suggests a Queer Vitalism to push the limits of how to understand humanness generally, and more specifically, how to understand processes of subjectification. She moves from a post-structuralist understanding toward the Deleuzian notion of practices of individuation and processes of becoming-imperceptible . In this essay, we draw on Queer Vitalism to show how it is possible to understand children's constructions of subjectivity in events of experimental dance practices for preschoolers. The analysis is performed in close interactions with video-films from these workshops transformed to still photography. We aspire to show how these practices can be understood as counter-power strategies in the enactment of an image of a Monstrous Child. Such an image might transform the taken-for-granted image of the Child and preschool practices in subversive ways.